(untitled) (Physical Education, Health and Social Sciences, 2026)
Psychological stress significantly impairs male sexual performance, manifesting as erectile dysfunction, reduced libido, and impaired ejaculatory control. This review integrates evidence from modern biomedical research and traditional Unani medicine, highlighting overlapping mechanisms such as HPA axis hyperactivity, cortisol elevation, oxidative stress, and humoral imbalance. Modern studies quantify neuroendocrine and vascular disruptions, while Unani perspectives emphasize systemic balance, nerve vitality, and restoration of vital forces through adaptogenic herbs, dietary modifications, and regimental therapies. The review also evaluates intervention strategies, including pharmacological therapies, stress-reduction techniques, and Unani-based treatments, demonstrating that integrated approaches can synergistically improve sexual function, enhance adherence, and support holistic recovery. Gaps in high-quality, large-scale random trials remain, particularly for combined interventions, underscoring the need for rigorous research with objective physiological and clinical endpoints. This synthesis provides a framework for culturally sensitive, patient-centered strategies to manage stress-induced sexual dysfunction.